Doktrina nujne zmogljivosti in pravice intelektualne lastnine kot nujna zmogljivost - Dacar, Rok (Podjetje in delo, 2023)
In this article, the author clarifies the conditions for the application of the essential facilities doctrine in European Union competition law. Although the doctrine has been widely applied by the Court of Justice of the European Union, no uniform set of criteria for its application has been developed. Thus, the criteria for applying the doctrine vary for different types of allegedly essential facilities. The criteria for applying the doctrine in cases where the alleged essential facility is a materialised facility or service are relatively clear. However, the situation is different when the alleged essential facilities are intellectual property rights. Two different sets of criteria have been developed for the assessment of such situations, which differ greatly from each other. This creates legal uncertainty for both companies controlling potentially essential facilities and companies seeking access to those facilities under the doctrine. The contribution clarifies which set of conditions is probably generally applicable in such situations and points out to the necessity of the clarification of this question through case law.
Keywords: doktrina nujne zmogljivosti; Evropska unija; intelektualna lastnina; konkurenčno pravo; nujna zmogljivost; podjetja